I heard the owl call my name. - Craven, Margaret (Garden City, N.Y., Doubleday, 1973)
Amid the grandeur of the remote Pacific Northwest stands Kingcome, a village so ancient that, according to Kwakiutl myth, it was founded by the two brothers left on earth after the great flood. The Native Americans who still live there call it Quee, a place of such incredible natural richness that hunting and fishing remain a primary food source.
Keywords: Kwakiutl Indians -- Fiction; Priests -- Fiction; British Columbia -- Fiction; Adventure stories